THE CULTURAL POLICY AND DEVELOPMENT OF CIVIL SOCIETY UNDER DECENTRALIZATION POLITICS - Hanif Nurcholis (Faculty of Humanities, Jember University, 2014)
Since the 1998 Reform Era, the system of government in Indonesia has changed from centralization to decentralization. Under the decentralization system, some affairs of government are given to the local governments (provincial, regent/municipal), except five affairs: 1) abroad policy; 2) defense and security; 3) monetary and fiscal; 4) management of justice; and 5) religion. One of the decentralized affairs is culture affair. Then local governments regulate (regeling) and administer (bestuur) their autonomy. However, under the local governments, the culture has been reduced be traditional art, traditional fashion, ancient manuscript, museum, and tourism based on traditional customs. In this perspektive, the culture is not seen as a system of values and expressions of thinking, behavior, and artifacts of mankind. Consequently, the cultural policy on has no correlatation with the development of civil society in the local level. Keywords: decentralization policy, culture affair, traditional art, civil society